Influence of Bond Coat on Thermal Shock Resistance and Thermal Ablation Resistance for Polymer Matrix Composites - Zhou, Jiahui; Jiang, Jianing; Deng, Longhui; Huang, Jingqi; Yuan, Jieyan; Cao, Xueqiang (Frontiers in Materials, 2021)
Polymer matrix composites (PMCs) have been widely used in aerospace industry because of low density and high strength-to-weight ratio. However, the application of PMCs is still limited by poor abrasion resistance, weak oxidation resistance and low operation temperature. In this study, Cu (Al)/NiCrAlY/YSZ triple layer coating system was deposited on glass fiber reinforced polyimide matrix composites (FPM) by means of High Velocity Oxygen Fuel (HVOF) for metallic coatings and Atmospheric Plasma Spraying (APS) for YSZ coating. The influence of different bond coats and different thickness of the top coat on the thermal shock resistance and thermal ablation resistance of the coating system was investigated. Compared with Al particle, Cu particle has a high density and correspondingly a high kinetic energy during spraying by HVOF, resulting in a high bonding strength between the Cu coating and FPM substrate. In the thermal shock test, the coating Cu/NiCrAlY/YSZ has a much longer life than the coating Al/NiCrAlY/YSZ. After high-speed impact on the substrate, there is a great compressive stress at the interface, which makes a plastic deformation to the substrate, and the particles are closely embedded into the substrate to form a strong mechanical interlock. The coating system consisting of 50 m Cu, 50 m NiCrAlY and 200 m 8YSZ exhibited the best thermal shock resistance, thermal ablation resistance and bonding strength. The increase of the top coat thickness will lead to the increase of residual stress and the decrease of bonding strength. The failure mechanism of the coating is mainly attributed to the residual stress in the deposition process and the thermal stress caused by thermal expansion mismatch.